Strategies for the prevention of volleyball related injuries - Reeser, J. C.; Verhagen, E.; Briner, W. W.; Askeland, T. I.; Bahr, R. (British Journal of Sports Medicine, 2006)
Although the overall injury rate in volleyball and beach volleyball is relatively low compared with other team sports, injuries do occur in a discipline specific pattern. Epidemiological research has revealed that volleyball athletes are, in general, at greatest risk of acute ankle injuries and overuse conditions of the knee and shoulder. This structured review discusses both the known and suspected risk factors and potential strategies for preventing the most common volleyball related injuries: ankle sprains, patellar tendinopathy, and shoulder overuse.